Modulated Hepatic Expression of NF-kB and CCN1 Genes in a Breast Cancer Mouse Model Induced by DMBA and High-Fat Diet - Demes Chornelia Martantiningtyas; Raden Ghita Sariwidyantry; Hana Ratnawati; Teresa Lilliana Wargasetya; Ardo Sanjaya (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2025)
Background: The study investigates the combined effects of 7,12-dimethylbenz[a]anthracene (DMBA) and a high-fat diet (HFD) on hepatic gene expression in a breast cancer mouse model. Both DMBA and HFD are associated with oxidative stress, inflammation, and fibrosis, which may contribute to cancer progression.Methods: Female C57BL/6 mice were divided into three groups: standard diet (ND), ND + DMBA, and HFD + DMBA. Mice in the ND + DMBA and HFD + DMBA groups received DMBA injections weekly for six weeks. The HFD + DMBA group was also fed a high-fat diet for four weeks prior to DMBA administration. After a 12-week treatment period, liver tissues were collected and analyzed for NF-κB and CCN1/CYR61 gene expression using semi-quantitative RT-PCR.Results: The study revealed significant upregulation of NF-κB and CCN1/CYR61 expression in the ND + DMBA and HFD + DMBA groups compared to the control group. Notably, the HFD + DMBA group exhibited the highest expression levels of these genes, suggesting that the combination of HFD and DMBA synergistically exacerbates hepatic inflammation and fibrosis.Conclusion: The findings indicate that a high-fat diet in combination with carcinogen exposure can significantly enhance hepatic gene expression related to inflammation and fibrosis, highlighting the importance of dietary management in cancer prevention and treatment.